Reactivity descriptors for DNA bases and the methylation of cytosine. Issue 11 (14th November 2017) - Jerbi, Jihène; Springborg, Michael
Abstract: This work is devoted to the reactivity of DNA bases and base pairs. Various global molecular descriptors for reactivity were studied in addition to local descriptors for Cytosine and Cytosine‐Guanine base pairs using three different ways of analysing the charge distribution. The process of methylation was selected since it is very important during the cell formation at the embryonic state and since much is already known about this system making an assessment of the quality of the theoretical approaches possible. The results reveal that Cytosine is the least reactive molecule among the bases although it can be attacked by the DNMT enzyme while paired with Guanine. Amain finding of the present work is, however, that by analysing the Fukui function and a dual descriptor we can rationalise that carbon at position 5 of Cytosine is the most favorable site for the methyl attack. Abstract : Enzymatic methylation of DNA involves the selective attack on a cytosine site, where the probability of the methylation increases if the base is paired with guanine. First‐principles calculations provide an insight into the local reactivity of cytosine and the C‐G base pair, helping to unveil the mystery of the cytosine selectivity of the reaction.